PERBEDAAN KUALITAS KEPUTUSAN DITINJAU DARI CARA BERPIKIR SECARA CONSCIOUS DAN UNCONSCIOUS THOUGHT - Letisa Biantong Parura; Lukman; Resekiani Mas Bakar (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
Decision quality is the result obtained from the decision-making process influenced by the way of thinking used (conscious and unconscious thought). This experimental research consisted of two groups, namely conscious thought and unconscious thought groups. This study aims to determine whether there is a difference in the quality of the decision to choose electronic products (laptops) between participants who think consciously (conscious thought) and unconsciously (unconscious thought). Participants in this research were 53 students in Makassar City (18-25 years). This study used the experimental method between-subjects design, randomized two groups design. The results of data analysis using Mann Whitney U showed a significance value (p) of 0.001 (p < 0.05). The results of the study show that there are differences in the quality of the decision to choose electronic products (laptops) for participants who think consciously (conscious thought) and unconsciously (unconscious thought). Participants in the unconscious thought group produced objectively better-quality decisions than participants in the conscious thought group. This research contributes to complex decision-making that can generate good quality decisions objectively when individuals rely on unconscious thought processes.